2014
DOI: 10.1002/jhm.2221
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of inpatient hypoglycemia with a real‐time informatics alert

Abstract: BACKGROUND Severe hypoglycemia (SH), defined as a blood glucose (BG) <40 mg/dL, is associated with an increased risk of adverse clinical outcomes in inpatients. OBJECTIVE To determine whether a predictive informatics hypoglycemia risk‐alert supported by trained nurse responders would reduce the incidence of SH in our hospital. DESIGN A 5‐month prospective cohort intervention study. SETTING Acute care medical floors in a tertiary care academic hospital in St. Louis, Missouri. PATIENTS From 655 inpatients on des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 33 publications
0
35
0
1
Order By: Relevance
“…Prior studies have found detection of hypoglycemia using glycemic control monitoring with computerized systems in hospital settings to be an efficient method of surveillance . To the best of the knowledge of the authors of the current study, this is the first study to prospectively use a computerized clinical surveillance system to detect and determine the incidence of drug‐associated hypoglycemia in NHs.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Prior studies have found detection of hypoglycemia using glycemic control monitoring with computerized systems in hospital settings to be an efficient method of surveillance . To the best of the knowledge of the authors of the current study, this is the first study to prospectively use a computerized clinical surveillance system to detect and determine the incidence of drug‐associated hypoglycemia in NHs.…”
Section: Discussionmentioning
confidence: 93%
“…Prior studies have found detection of hypoglycemia using glycemic control monitoring with computerized systems in hospital settings to be an efficient method of surveillance. [9][10][11][12] To the best of the knowledge of the authors of the current study, this is the first study to prospectively use a computerized clinical surveillance system to detect and determine the incidence of drug-associated hypoglycemia in NHs. This study is responsive to the OIG's recommendations to raise awareness of ADEs in NH residents receiving postacute care by mirroring methods used to promote medication safety and adverse event detection in the hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…Only two other algorithms that aim to identify patients at risk of hypoglycaemia exist for inpatients with diabetes, but these were not externally validated [27,28]. Only two other algorithms that aim to identify patients at risk of hypoglycaemia exist for inpatients with diabetes, but these were not externally validated [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the results of the present analysis show that the model is both temporally and externally valid: it performed well in both more recent data from the original hospital (UHB) and in other hospitals with sociodemographically The strengths of the present study include the external validation across two distinctly different hospital settings, datasets with large numbers of patients and events, robust methodology including a number of sensitivity analyses, and being the first study to derive and validate a prediction model to identify adverse events in hospitalized patients with diabetes based on routinely collected data close to the time of admission. Only two other algorithms that aim to identify patients at risk of hypoglycaemia exist for inpatients with diabetes, but these were not externally validated [27,28]. Validation of the model is, however, limited to hospitals in the UK, and data from Ipswich Hospital had limitations that prevented us from optimally demonstrating the performance in a district general hospital setting.…”
Section: Discussionmentioning
confidence: 99%
“…The alert was pilot tested at select nursing stations at BJC's adult academic hospital in 2011, with a subsequent 68% reduction of severe hypoglycemia in high-risk patients that year. 13 A further reduction of 19% was seen in 2012, when the alert system was implemented on all acute and progressive-care nursing units. 14 With the approval of medical and administrative leaders at each BJC hospital, diabetes educators, nurses, and pharmacists were trained to respond to this alert at all remaining BJC hospitals.…”
Section: Development Of Targeted Risk Alertsmentioning
confidence: 98%